RETRACTED: THE DEVELOPMENT OF PROJECT BASED LEARNING E-MODULE FOR THE SUBJECT OF COMPUTER GRAPHICS - Luh Astiti; I Gede Mahendra Darmawiguna; Gede Saindra Santyadiputra (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Teknologi dan Kejuruan entitled “The Development of Project Based Learning E-Module for the Subject of Computer Graphics”, Vol 23, No 2, pp. 175-183, October 2016  DOI: http://dx.doi.org/10.21831/jptk.v23i2.13185This paper has been found to be in violation of the Jurnal Pendidikan Teknologi dan Kejuruan Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika (KARMAPATI) ISSN: 2252-9063, Vol. 4, No. 5, 2015.The document and its content has been removed from Jurnal Pendidikan Teknologi dan Kejuruan, and reasonable effort should be made to remove all references to this article.